Teachers’ perspectives on the use of arabic loanwords in hausa in the teaching of arabic to Nigerian students - Mainasara, Nasiru (2021)
Previous studies found that Hausa-speaking Arabic learners at the Umaru Ali Shankafi polytechnic of Sokoto and Shehu Shagari College of Education in Sokoto State Nigeria lacked productive skills (speaking and writing) and receptive skills (listening and reading), leading us to conclude that the problem is real and exists in this society and that the majority of these problems are hidden in the weaknesses of the educational syllabus that follows the traditional curriculum, as well as failure to pay attention to the needs and interests of these students. The majority of prior research focused on the importance of Arabic loanwords in resolving the problem of poor language skills and did not investigate the efficiency of Arabic loanwords in this regard according to the perspectives of Arabic language teachers. The goal of this study is to examine Arabic language teachers' perspectives on the impact of loanwords in Arabic on teaching the productive skills (writing and speaking) and reception skills (listening and reading), as well as to determine the most effective skills in using Arabic loanwords among Hausa speakers. In addition to discover a relationship between the use of Arabic loanwords in the teaching of the four skills and their effectiveness in inspiring students. For that purpose, the study uses a quantitative technique, using Arabic language teachers from the Umar Ali Shankafi polytechnic in Sokoto and Shehu Shagari College of Education as the study sample. The research is based on Schumann's (1975) principles for second language acquisition and teaching, which were developed based on the three factors that influence second language learning. The results of the study are analysed through the use of statistical methods, both descriptive and inferential, where average calculations, standard deviations, and ratios are used to analyse the viewpoint of Arabic teachers in teaching the four language skills using Arabic loanwords, and the descriptive results were relied upon to conclude the most effective skills in the four language skills, and the Spearman correlation coefficient is used to discover the relationship between the use of Arabic loanwords in learning the four language skills and its effectiveness in motivating learners. The findings of the study demonstrate that Arabic loanwords have a substantial impact on teaching productive skills (writing and speaking) and receptive skills (hearing and reading) among Hausa-speaking Arabic learners, with the mean value ranging between (3.71-4.18). The findings of the third goal indicate that the speaking skill ranked first in effectiveness, with a total average (mean) of its items that reach (4.31), while the listening skill in second spot, with an average mean (3.99), followed by reading skill and ranked as the third position with a mean (3.48). Meanwhile the writing skill is ranked as last position with average mean (3.32). In terms of the fourth goal, the Spearman correlation coefficient highly significant at (α=0.05) which means the relation between the use of Arabic loanwords and learning motivation, is highly significant with the (x) (Arabic loanwords) having a high impact on (y) learning motivation.